Modelo de autoguía audiovisual interpretativa de historia natural para público naturalista, con el ejemplo de caso Místico Arenal Hanging Bridges Park, La Fortuna, 2016 - Calvo-Vargas, Indira María (Instituto Tecnológico de Costa Rica, 2016)
This project was developed as a requirement to get the degree of Bahiller as a Sustainable Rural Tourism Manager, at the Costarrican Institute of Technology, Santa Clara campus. The project was carried out in the main trail of the site Mistico Arenal Hanging Bridges Park with the objective of generating a proposal of an audiovisual self-guided interpretive model for naturalist public First the public Mistico Arenal Hanging Bridges Park was characterized, through a survey which had eight direct questions to know the age of tourists, nationality, mode of visit, why were traveling, the means by which they learned of the site, the main activity relizaban by visiting sites like Mistico Arenal Hanging Bridges Park and and their opinion about the creation of an interpretative instrument for the trails of the site. Once the public was characterized, the self-guided model was created by the literature and conceptual review of theEnvironmental Interpretation (IA) and the design of interpretive models. Subsequently, the biodiversity of the site was characterized through field visits to identify espcies of flora and fauna of the main trail, observe behaviors between species and to establish the points where the Interpetación could be realized. Also interviews to the site administadores about the existence of databases of biodiversity from the park. Finally, after analyzing the data, the self-guided model was applied to Mistico Arenal Hanging Bridges Park, creating two designs for the site which share the content, but vary in language and format
Proyecto de Graduación (Bachiller en Gestión del Turismo Rural Sostenible) Instituto Tecnológico de Costa Rica, Escuela de Idiomas y Ciencias Sociales, 2016
Keywords: Guía de viaje; Turísmo ecológico